Characterization of Ferredoxin-Dependent Biliverdin Reductase PCYA1 Reveals the Dual Function in Retrograde Bilin Biosynthesis and Interaction With Light-Dependent Protochlorophyllide Oxidoreductase LPOR in Chlamydomonas reinhardtii - Zhang, Weiqing; Zhong, Huan; Lu, Hui; Zhang, Yuxiang; Deng, Xuan; Huang, Kaiyao; Duanmu, Deqiang (Frontiers in Plant Science, 2018)
Bilins are linear tetrapyrroles commonly used as chromophores of phycobiliproteins and phytochromes for light-harvesting or light-sensing in photosynthetic organisms. Many eukaryotic algae lack both phycobiliproteins and phytochromes, but retain the bilin biosynthetic enzymes including heme oxygenase (HO/HMOX) and ferredoxin-dependent biliverdin reductase (FDBR). Previous studies on Chlamydomonas reinhardtii heme oxygenase mutant (hmox1) have shown that bilins are not only essential retrograde signals to mitigate oxidative stress during diurnal dark-to-light transitions, they are also required for chlorophyll accumulation and maintenance of a functional photosynthetic apparatus in the light. However, the underlying mechanism of bilin-mediated regulation of chlorophyll biosynthesis is unclear. In this study, Chlamydomonas phycocyanobilin:ferredoxin oxidoreductase PCYA1 FDBR domain was found to specifically interact with the rate-limiting chlorophyll biosynthetic enzyme LPOR (light-dependent protochlorophyllide oxidoreductase). PCYA1 is partially associated with chloroplast envelope membrane, consistent with the observed export of bilin from chloroplast to cytosol by cytosolic expression of a bilin-binding reporter protein in Chlamydomonas. Both the pcya1-1 mutant with the carboxyl-terminal extension of PCYA1 eliminated and efficient knockdown of PCYA1 expression by artificial microRNA exhibited no significant impact on algal phototrophic growth and photosynthetic proteins accumulation, indicating that the conserved FDBR domain is sufficient and minimally required for bilin biosynthesis and functioning. Taken together, these studies provide novel insights into the regulatory role of PCYA1 in chlorophyll biosynthesis via interaction with key Chl biosynthetic enzyme.